Reactive oxygen species (ROS) and response of antioxidants as ROS-scavengers during environmental stress in plants - Das, Kaushik; Roychoudhury, Aryadeep (Frontiers in Environmental Science, 2014)
Reactive oxygen species (ROS) were initially recognized as toxic by-products of aerobic metabolism. In recent years, it has become apparent that ROS plays an important signaling role in plants, controlling processes such as growth, development and especially response to biotic and abiotic environmental stimuli. The major members of the ROS family include free radicals like O2● −, OH● and non-radicals like H2O2 and 1O2. The ROS production in plants is mainly localized in the chloroplast, mitochondria and peroxisomes. There are secondary sites as well like the endoplasmic reticulum, cell membrane, cell wall and the apoplast. The role of the ROS family is that of a double edged sword; while they act as secondary messengers in various key physiological phenomena, they also induce oxidative damages under several environmental stress conditions like salinity, drought, cold, heavy metals, UV irradiation etc., when the delicate balance between ROS production and elimination, necessary for normal cellular homeostasis, is disturbed. The cellular damages are manifested in the form of degradation of biomolecules like pigments, proteins, lipids, carbohydrates and DNA, which ultimately amalgamate in plant cellular death. To ensure survival, plants have developed efficient antioxidant machinery having two arms, (i) enzymatic components like superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), guaiacol peroxidase (GPX), glutathione reductase (GR), monodehydroascorbate reductase (MDHAR) and dehydroascorbate reductase (DHAR); (ii) non-enzymatic antioxidants like ascorbic acid (AA), reduced glutathione (GSH), α-tocopherol, carotenoids, flavonoids and the osmolyte proline. These two components work hand in hand to scavenge ROS. In this review, we emphasize on the different types of ROS, their cellular production sites, their targets, and their scavenging mechanism mediated by both the branches of the antioxidant systems, highlighting the potential role of antioxidant